BS EN 13656. Soil, treated biowaste, sludge and waste. Digestion with a hydrochloric (HCl), nitric (HNO3) and tetrafluoroboric (HBF4) or hydrofluoric (HF) acid mixture for subsequent determination of elements. (12th September 2019) - British Standards Institution,
No abstract available